Strategi Manajemen Kinerja Dalam Meningkatkan Efektivitas Operasional Pada Perusahaan Asuransi - Thasya Virdinia; Zainarti Zainarti (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This article aims to identify and analyze effective performance management strategies to enhance operational effectiveness in insurance companies. The study employs a qualitative descriptive method with a case study approach on a leading insurance company in Indonesia. Data were collected through in-depth interviews, observations, and analysis of internal company documents. The results indicate that the implementation of a balanced scorecard, the adoption of digital technology in operational processes, and the continuous development of human resource competencies are key factors supporting optimal performance achievement. These strategies have been proven to improve efficiency, strengthen customer service, and maintain the company’s competitiveness amidst the dynamic and competitive insurance industry.